Brachial artery pseudoaneurysm secondary to inadvertent arterial puncture (Revista Argentina de Cirugía, 2021)
Brachial artery pseudoaneurysms are rare but can be associated with severe complications as ischemia of the upper extremity. We report a case of a brachial artery pseudoaneurysm in the crease of the elbow presenting as a pulsating mass with progressive growth over the past year.The ipsilateral hand was sightly cold and presented paresthesia. The lesion was due to inadvertent arterial puncture during venipuncture. The pseudoaneurysm was successfully treated with surgical resection and vascular reconstruction with a brachial to ulnar artery bypass and brachial to radial artery bypass with saphenous vein graft. The different therapeutic options available for brachial artery pseudoaneurysms are discussed, considering the anatomic characteristics and patients’ symptoms
Keywords: pseudoaneurysm; false aneurysm; brachial artery injuries; iatrogenic disease; upper limb ischemia